Struktur Vegetasi dan Simpanan Karbon Hutan Hujan Tropika Primer DI Batang Toru, Sumatra Utara - Onrizal, Onrizal; Ismail, Ismail; Perbatakusuma, Erwin A.; Sudjito, Herwasono; Supriatna, Jatna; Wijayanto, Iwan H. (Perhimpunan Biologi Indonesia, 2008)
ABSTRACTVegetation structure and carbon stock of primary tropical rain forest at Batang Toru, NorthSumatra. Deforestation and forest degradation contribute for 20 to 25 percent of annual totalcarbon dioxide (CO2) emissions and to be one of substantial factor of climate change or globalwarming. Avoided deforestation into carbon-market regime by reducing emission fromdeforestation and forest degradation (REDD) scheme has been agreed on COP 13 of UNFCCCthat was held in Bali on December 2007. REDD application need reliable scientific basic aboutthe amount of carbon storage in well managed natural forest. The aims of this research were todetect vegetation structure and to estimate aboveground biomass, carbon stock and CO2absorption of primary tropical rain forest at Key Biodiversity Area of Batang Toru ForestBlock, North Sumatra Province by existing allometric equation. We designed 20 sampling plotsof 20 x 20 m in two forest area, i.e. Aek Game-game forest and Aek Silemes forest. All trees 5 cmat diameter at breast height (dbh) and above were measure and identified. From the study, thedistribution of diameter class formed âLâ curve which mean an indication as balanced forest.The aboveground biomass of the forest is 544.4 to 583.0 t/ha in Aek Silemes forest and 604.5 to613.6 t/ha Aek game-game forest. It is equivalent with 272.2 to 291.5 t C/ha or 999.0 to 1,069.9 tCO2/ha in Aek Silemes forest and 302.2 to 306.8 t C/ha or 1,109.2 to 1,125.9 t CO2/ha in Aekgame-game forest. More of carbon stock (>46% for Aek Silemes forest and >58% for Aek gamegameforest) saved within dbh of trees 50 cm and above. Therefore, sustainable managementof forest ecosystem is very important to reduce CO2 emission from deforestation and forestdegradation and to improve the function of forest ecology and economy.Keywords: aboveground biomass, carbon stock, CO2, primary tropical rain forest, BatangToru-North Sumatra